Subducted, detached, and torn slabs beneath the Greater Caucasus. (March 2015) - Mumladze, Tea; Forte, Adam M.; Cowgill, Eric S.; Trexler, Charles C.; Niemi, Nathan A.; Burak Yıkılmaz, M.; Kellogg, Louise H.
Graphical abstract: Abstract: The Greater Caucasus Mountains contain the highest peaks in Europe and define, for over 850 km along strike, the leading edge of the second-largest active collisional orogen on Earth. However, the mechanisms by which this range is being constructed remain disputed. Using a new database of earthquake records from local networks in Georgia, Russia, and Azerbaijan, together with previously published hypocenter locations, we show that the central and eastern Greater Caucasus Mountains are underlain by a northeast-dipping zone of mantle seismicity that we interpret as a subducted slab. Beneath the central Greater Caucasus (east of 45°E), the zone of seismicity extends to a depth of at least 158 km with a dip of ∼40°NE and a slab length of ∼130–280 km. In contrast, beneath the western GC (west of 45°E) there is a pronounced lack of events below ∼50 km, which we infer to reflect slab breakoff and detachment. We also observe a gap in intermediate-depth seismicity (45–75 km) at the western end of the subducted slab beneath the central Greater Caucasus, which we interpret as an eastward-propagating tear. This tear coincides with a region of minimum horizontal convergence rates between the Lesser and Greater Caucasus, as expected in a region of active slab breakoff. Active subduction beneath the eastern Greater Caucasus presents a potentially larger seismic hazard than previously recognized and may explain historical records of large magnitude (M 8) seismicity in this region.